Assessment of rainwater harvesting and maintenance practice for better drinking water quality in rural areas - Dung A. Dao (IWA Publishing, 2021)
In many areas of the world, rainwater has been collected and consumed by people. Our research aims to assess the use of rainwater and the impact of operation and maintenance activities of the rainwater system on drinking water quality in rural areas where there is no access to a public drinking water system. Through the questionnaire, direct visits, interviews and sampling of water at surveyed households (HHs), it was found that 100 and 98% of surveyed HHs used rainwater for drinking and cooking, respectively. Nearly, 80% of them were aware of the necessity of frequent reservoir cleaning as well as first-flush removal. Cleaning the water reservoir had a significant impact on water quality, in particular the total dissolved solids (p-value < 0.05). The use of strainers and more frequency of cleaning the catchment roofs and gutters would make the lower turbidity in water. However, the use of strainers would reduce the dissolution of oxygen in the reservoirs. A recommendation on the frequency of maintaining the rainwater harvesting systems was proposed after assessment of the operation and maintenance behaviors at surveyed HHs. HIGHLIGHTS This is the first study on assessment of the operation and maintenance of rainwater harvesting (RWH) systems at the household scale in the rural area.; Most of them (>90%) were aware of frequent reservoir cleaning as well as eliminating the first rains.; The majority (95%) of households did not add disinfectant in the reservoirs but boiled water or filtered with membrane units before drinking.; Harvested rainwater showed significantly higher pH, dissolved oxygen (DO) and coliforms but much less dissolved solids than groundwater.;